(3HdhZ GdeQGe aj JGQjN OhdI ehdGfG HgQGes - (3GdoenWnqjH , eMeO Hf jMji,J (B990 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CWdY CfhGQ GdYOhegO CMcGeg s
(3BNQgG (B:s
(3jSQ Gddg WQjbg Ydi CMSf MGd hSgd Ydjg eG jQLhg ef UdGM GdCMhGd s
(3YGT GdeDda fMh SfI (B990 (3aI RHjOs
(3ahJhZQGa Yf fSNI HGQjS s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B141 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B111s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B401 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B50 s
Keywords: (3GdJGQjNs